Pre-supplementation of Crocus sativus Linn (saffron) attenuates inflammatory and lipid peroxidation markers induced by intensive exercise in sedentary women - Mohammad Hosseinzadeh, Hossein TaheriChadorneshin, Mahboobe Ajam-Zibad, Seyed-Hosein Abtahi-Eivary (Journal of Applied Pharmaceutical Science, 2017)
Antioxidant and anti-inflammatory actions of Crocus sativus Linn (saffron) in relation to intensive exercise need to be studied. This study aimed to investigate the effect of four weeks of saffron supplementation on serum levels of tumor necrosis factor alpha (TNF-α), as a marker of inflammation, malondialdehyde (MDA), as a marker of lipid peroxidation, and levels of Lactate dehydrogenase (LDH) and creatine kinase (CK), as two markers of muscle damage, in sedentary women following intensive exercise. After a 4-week period of supplementation (30 mg/day), the healthy inactive young women performed one bout of acute resistance exercises at 85 % of one-repetition maximum. Using commercial kits, TNF-α and MDA levels were measured using ELISA method. In addition, LDH and CK were measured by photometric method. Data were statistically analyzed by one-way ANOVA (P
Keywords: Intensive resistance exercise, Saffron supplementation, Tumor necrosis factor alpha, Malondialdehyde, Lactate dehydrogenase, Creatine kinase, Inactive women.